Positivising Sharī’a In National Regulation Through Maqasid Approach (Studies on Government Policy in Handling of Foreign Refugees in Indonesia) - Rohmad Adi Yulianto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The problematic of humanism in many countries results a phenomenon of trans-national refugee migration. Indonesia is one of country which received a massif influx of refugee wave aiming to obtain an asylum. This study discussed the policy of handling refugee in Indonesia from the maqasid sharia as perspective. Maqasid sharia, as one of the Islamic law methodological approaches in order to understanding social phenomena which positioned the interest (maslaha) as the core treatise. This study aimed to explain that the interaction between maqasid sharia as perspective and the development of national regulation, including the regulation in handling refugees, results three models of policy (instructive, integrative, and adaptive). Instructive policy implemented through taqnīn model, which is issued by the state authority as positive norm. Integrative policy implemented through eclectic model, adopted the finest part from both national law and Islamic law. Adaptive policy implemented when important elements of Islamic law affirmed national policy which contained fundamental principle of universal humanism as part of sharī’a.